Examining Equity Sensitivity: An Investigation Using the Big Five and HEXACO Models of Personality - Woodley, Hayden J. R.; Bourdage, Joshua S.; Ogunfowora, Babatunde; Nguyen, Brenda (Frontiers in Psychology, 2016)
The construct of equity sensitivity describes an individual’s preference about his/her desired input to outcome ratio. Individuals high on equity sensitivity tend to be more input oriented, and are often called “Benevolents”. Individuals low on equity sensitivity are more outcome oriented, and are described as “Entitleds”. Given that equity sensitivity has often been described as a trait, the purpose of the present study was to examine major personality correlates of equity sensitivity, so as to inform both the nature of equity sensitivity, and the potential processes through which certain broad personality traits may relate to outcomes. We examined the personality correlates of equity sensitivity across three studies (total N = 1170), two personality models (i.e., the Big Five and HEXACO), the two most common measures of equity sensitivity (i.e., the Equity Preference Questionnaire and Equity Sensitivity Inventory), and using both self and peer reports of personality (in Study 3). Although results varied somewhat across samples, the personality variables of Conscientiousness and Honesty-Humility, followed by Agreeableness, were the most robust predictors of equity sensitivity. Individuals higher on these traits were more likely to be Benevolents, whereas those lower on these traits were more likely to be Entitleds. Although some associations between Extraversion, Openness, and Neuroticism and equity sensitivity were observed, these were generally not robust. Overall, it appears that there are several prominent personality variables underlying equity sensitivity, and that the addition of the HEXACO model’s dimension of Honesty-Humility substantially contributes to our understanding of equity sensitivity.